Clinical Study of Optic Neuropathies (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Optic neuropathy is a frequent cause of vision loss encountered by ophthalmologist. Thediagnosis is made on clinical grounds. The history often points to the possible etiology of the optic neuropathy.A rapid onset is typical of demyelinating, inflammatory, ischemic and traumatic causes. A gradual coursepoints to compressive, toxic/nutritional and hereditary causes. The classic clinical signs of optic neuropathyare visual field defect, dyschromatopsia, and abnormal papillary response. Study objectives were to studyetiological factors causing optic neuropathies.Materials and Method: This analytical study was performed in Krishna Medical College Hospital, Karadfor a period of months. The initial examination was started with anterior segment examination on slit lampand fundus examination with direct ophthalmoscope. The material for the present study consists of 65 opticneuropathy patients during the 18 months period from November 2017 to May 2019.Results: During this study, in Krishna Hospital karad we noticed that glaucomatous optic neuropathy is themost common type of optic neuropathy and traumatic optic neuropathy is the second most type.Conclusion: Glaucoma being frequent cause of vision loss , is unfortunately not diagnosed at early stageand as age advances the risk of glaucoma increases also hypertension is one of the risk factors, so routinelyevery patient >40 years of age is to be assessed for glaucoma by noting optic disc changes and intra ocularpressure. If necessary Dynamic Perimetry is to be done for further evaluation.